Ibrutinib and rituximab induced rapid response in refractory Richter syndrome. Issue 7 (5th June 2015) - Lamar, Zanetta; Kennedy, LeAnne; Kennedy, Brooke; Lynch, Mary; Goad, Amanda; Hurd, David; McIver, Zachariah
Key Clinical Message We report a 53‐year‐old man diagnosed with Richter syndrome. He was heavily pretreated and was refractory to prior therapy. He received rituximab and ibrutinib, and achieved a significant response after 1 month of therapy. Our case illustrates the importance of investigation of rituximab and ibrutinib in Richter's syndrome.